Management Game Theory - Sun, Shaorong (Springer Singapore, 2018)
This book primarily addresses various game theory phenomena in the context of management practice. As such, it helps readers identify the profound game theory principles behind these phenomena. At the same time, the game theory principles in the book can also provide a degree of guidance for solving practical problems. As one of the main areas in management research, there is already an extensive body of literature on game theory. However, it remains mainly theoretical, focusing on abstract arguments and purely numerical examples purely. This book addresses that gap, helping readers apply game theory in their actual management or research work. .